“Evaluación de rendimiento de 4 variedades de arroz (oryza sativa L.) bajo riego mayo distrito de cacatachi” - Flores Vásquez, Artemio (2002)
The present work was developed between January · and October of the 2000, in the object of evaluating the effect of fann zero in yield of 4 varieties of commercial of rice one cari-ies out an experimend Found 2ª of the UNSM located in the District of Cacatachi, county and Department of San Martin, located geographically at 06º 22 of south latitude, 76.12 longitude west, with an altitude of 330 m.s.n.m., you uses the statistical design of (DBCR) with 04 treatments and 04 repetitions. The system of farm zero consists on carrying out the following activities: To give a heavy watering to facilitate the germination of rice remainder and overgrowths, to eliminate the overgrowths then with glifosato, to carry out another watering before the 1 volley of the seed. Certified seed was used and it was volleyed pre-germinated to reason of 80 Kg. /Ha., in each variety parcels of 50 m2 were used in which were carried out manual deshierbes and all the other activities, they are the same ones that in the traditional system of transplant. In the cultivation intermittent waterings and periodic floods were used in required moments, they were fertilized in 03 stages with complementary <lose of nitrogen, match and potassium with the fonnula 100:60:30 to the 15 days of the 1 volley of the seed the first nitrogen <lose, the second at the 35 days and the third tú the 65 days. The match was applied in 02 <lose together with the first one and the second nitrogenada fertilization the K20 together with the third nitrogen <lose, The obtained results indicate that among the studied treatments significant difference existed for the grain yield on going out the Moorish variety with 7 813.6 Kg. /Ha. followed High May with 7 618.26 Kg. /Ha.; Capirona in the third place with 6 690.34 Kg. /Ha. and in the fourth place with the smallest yield Huallaga Inía with 6 051 Kg. /Ha adjusted yield to 14% ofhumidity.